PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH PLASTIK PT. INDAH KIAT DI DESA PERAWANG KABUPATEN SIAK - Giawa, Erwin Lorencius; Irja, Desti; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study examines the shortage of jobs in the village of Perawang, especially for housewives who usually do not work and sit alone at home without earning money to meet the needs of their families, and the large amount of plastic waste produced by Indah Kiat point . The purpose of this study was to determine community empowerment by PT management. Indah Kiat at Perawang Village, Siak Regency This type of research is descriptive naturalistic with a qualitative approach. The process of data collection is carried out by interviewing 6 research themes, namely 3 key informants, 2 control people and 1 observer informant including documentation. Based on the results of interviews, the researchers found 4 indicators, namely: (1) Planning, (2) Organizing, (3) Implementation, (4) Supervision. The study of the 4 indicators is very useful to understand how communities can be optimally encouraged by plastic waste management to help people find jobs, expertise and a place to make money so that they can meet their daily needs.Key Words: Empowerment, Management, Plastic Waste